The Absence of NOD1 Enhances Killing of Aspergillus fumigatus Through Modulation of Dectin-1 Expression - Gresnigt, Mark S.; Jaeger, Martin; Subbarao Malireddi, R. K.; Rasid, Orhan; Jouvion, Grégory; Fitting, Catherine; Melchers, Willem J. G.; Kanneganti, Thirumala-Devi; Carvalho, Agostinho; Ibrahim-Granet, Oumaima; van de Veerdonk, Frank L. (Frontiers in Immunology, 2017)
One of the major life-threatening infections for which severely immunocompromised patients are at risk is invasive aspergillosis (IA). The increasing antifungal resistance and poor outcome despite the current treatment options, highlights the need for novel therapeutic strategies to improve outcome of patients with IA. In the current study, we investigated whether and how the intracellular pattern recognition receptor NOD1 is involved in host defense against Aspergillus fumigatus. When exploring the role of NOD1 in an experimental mouse model, we found that Nod1-/- mice were protected against IA and demonstrated reduced fungal outgrowth in the lungs. We found that macrophages derived from bone marrow of Nod1-/- mice were more efficiently inducing reactive oxygen species and cytokines in response to Aspergillus. Most strikingly, these cells were highly potent in killing A. fumigatus compared to wild type cells. In line, human macrophages in which NOD1 was silenced demonstrated augmented Aspergillus killing and NOD1 stimulation decreased fungal killing. The differentially altered killing capacity of NOD1 silencing versus NOD1 activation was associated with alterations in dectin-1 expression, with activation of NOD receptors reducing dectin-1 expression. Furthermore, we were able to demonstrate that Nod1-/- mice have elevated dectin-1 expression in the lung and bone marrow, and silencing of NOD1 in human macrophages also increases dectin-1 expression. The enhanced dectin-1 expression may be the mechanism of enhanced fungal killing of Nod1-/- cells and human cells in which NOD1 was silenced, since blockade of dectin-1 reversed the augmented killing. Collectively, our data demonstrate that NOD1 receptor plays an inhibitory role in the host defense against Aspergillus. This provides a rationale to develop novel immunotherapeutic strategies for treatment of aspergillosis that target the NOD1 receptor, to enhance the efficiency of host immune cells to clear the infection by increasing fungal killing and cytokine responses.